Mind Covid, Remember Mask" To Reduce Corona Spreading (A Case Study In The Johan Pahlawan Sub-District, Meulaboh City, West Aceh) - Musliyadi; Irmayanti (International Journal of Science, Technology & Management, 2023)
The coronavirus spread has been the main issue among Acehnese people since it occurred. Every day, people get infected; some people also are starting to recover from the coronavirus. The governments have been working to reduce the risked people and infected victims by providing various personal protective equipment and educating the public about the virus and its threats. Those all require society to obey them, such as wearing masks to avoid being infected or transmit to other people. Until now, the spread of the coronavirus is also very high trending. The Covid-19 task force in Jakarta on February 16th, 2021 recorded that the ratio of coronavirus cases has reached 38.34 percent. This figure shows the highest daily record since the pandemic took place. This study used a descriptive method with a qualitative approach. Data collection was performed by interviewing several communities in the Johan Pahlawan sub-district, monitoring and observing in the field, and reading relevant sources. The study found a low level of community compliance with health protocols. The use of masks is still very lacking; people only wear masks when raids are carried out on the streets by joint government officials